Urban Expansion and Erosion Processes in an Area of Environmental Protection in Nova Lima, Minas Gerais State, Brazil - Ercoli, Rafael Falci; Matias, Vandeir Robson da Silva; Zago, Valéria Cristina Palmeira (Frontiers in Environmental Science, 2020)
The growth of the real estate market is considered one of the leading economic indicators of city development. The pressure for new sites for the construction of buildings and houses causes significant and severe socio-environmental impacts. The municipality of Nova Lima is conurbated with Belo Horizonte, the capital of Minas Gerais State, Brazil. In recent decades, the municipality of Nova Lima has been attracting real estate developers of luxury housing because of its favored location in a valley surrounded by mountain ranges with stunning landscapes. This study aimed to evaluate the emergence and evolution of erosive processes in a region of high real estate pressure in the municipality of Nova Lima, Minas Gerais State, Brazil. The study site is considered an area of environmental protection, belonging to the “Cardoso” river basin, a tributary of the “das Velhas” river. The images of the area were obtained by an “unmanned aerial vehicle”, with flights performed in 2019. Orthomosaic, digital surface and elevation models were obtained from these images. Historical series of satellite imagery provided by Google Earth were also used, as well as a survey of secondary data on the use and soil occupation of the region. The intense expansion of the real estate sector in metropolitan areas put pressure on environmental preservation in peri-urban areas. In this study, erosion processes and gullies were observed as a result of the construction of luxury residences. Construction residues of the buildings were disposed on the floor of a valley, burying the source of the “Estrangulado” Stream. The appearance of gullies is attributed to a combination of factors such as the removal of vegetation cover, the irregular disposal of construction waste in an environmental protection area, an insufficient drainage system for rainwater, and the lack of water collection and treatment of domestic wastewater. Over the years, the dimensions of gullies have increased and can cause damage to the buildings there. Also, the soil and sediment washed away by the runoff will affect the volume and quality of water in a watershed that is essential for supplying the metropolitan region of Belo Horizonte, Minas Gerais, Brazil.